Review of Technology Acceptance Model Electronic Commerce Adoption: A Conceptual Framework: Examining the Effectiveness of the Technology Acceptance Model in E-commerce Adoption (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Technology has become integrated component of the business. All the stakeholders, executives and the researchers are trying to understand the online buying behavior of the consumers. E-commerce has become the viable means of conducting business activities. The acceptance of technology by the consumer has been an important field of study for almost over four decade. One model which is attracted the researchers worldwide is technology acceptance model. Anyone willing to understand the intentions of acceptance of E-commerce has to understand the technology acceptance model (TAM). The review of TAM can give a clear understanding to the researchers to determine the underlying component resulting into redefining and restructuring the model to be more effective and efficient in establishing the model. In this paper 20 publications on the E-commerce are reviewed. The author reviewed these studies to establish the applicability of TAM. The observations conclude that though the TAM is exceedingly cited model but the researchers have mixed opinion about its theoretical assumption and its actual effectiveness. It is concluded that TAM lack sufficient explanation and relevance to make it a well-established theory for the E- commerce community.